Is foliar flammability of woody species related to time since fire and herbivory in northwest Patagonia, Argentina? - Blackhall, Melisa (2012)
Question: In northwest Patagonia burning of fire-resistant forests creates a community-level positive feedback towards increased fire occurrence because of successional replacement by fire-prone shrublands. We hypothesize that variability in plant traits related to time since last fire and to herbivory by cattle may affect foliar flammability, thus providing a flammability-promoting mechanism operating at the level of individual plants. We examine how plant foliar traits affecting flammability vary across species and at sites recovering from recent fires (<15 yr) vs sites not affected by fire for > 50 yr, both in the presence and absence of cattle. Location: Nahuel Huapi National Park, northwest Patagonia, Argentina. Methods: We measured four foliar traits expected to affect flammability: leaf moisture, leaf size, specific leaf area and leaf strength, and conducted tests of ignitability (time to ignition and duration of combustion) on leaves of six common tall shrub and small tree species: non-palatable Lomatia hirsuta and Diostea juncea, moderately palatable Nothofagus antarctica and Schinus patagonicus and highly palatable Maytenus boaria and Ribes magellanicum. We used ANOVA and PCA to examine potential relationships among species flammability traits, time since fire and presence or absence of cattle. Results: At plant level, variability in flammability-related foliar properties is strongly and consistently related to time since last fire, whereas effects of cattle are more variable across species and treatments. In comparison with unburned forests, the dominant woody species at shrubland sites showed reduced leaf moisture, leaf size and specific leaf area. Under pressure from cattle, N. antarctica, one of the most important woody species in these shrublands, showed changes in some foliar traits expected to enhance flammability (e.g. shorter time to ignition) but overall the influence of cattle on flammability was not consistent. Conclusions: The current study demonstrates that plant foliar traits vary between recently burned and unburned sites, and that these variations may enhance foliar flammability in shrubland communities. We hypothesize that variability in plant traits related to time since last fire and to herbivory by cattle may affect foliar flammability, thus providing a flammability-promoting mechanism operating at the level of individual plants. In northwestern Patagonia, Argentina, plant foliar traits vary between recently burned and unburned sites, and these variations may enhance foliar flammability in shrubland communities.